2016
DOI: 10.1002/2016jd025653
|View full text |Cite
|
Sign up to set email alerts
|

A Lagrangian analysis of cold cloud clusters and their life cycles with satellite observations

Abstract: Cloud movement and evolution signify the complex water and energy transport in the atmosphere‐ocean‐land system. Detecting, clustering, and tracking clouds as semicoherent clusters enable study of their evolution which can complement climate model simulations and enhance satellite retrieval algorithms, where there are gaps between overpasses. Using a cluster tracking algorithm, in this study we examine the trajectories, size, and brightness temperature of millions of cloud clusters over their lifespan, from in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 53 publications
0
8
0
1
Order By: Relevance
“…In addition, given the limitations of the study period, some results are calculated by gathering all the events from all the valid gridboxes across China, while a future study with a sufficient number of samples should further investigate the region‐specific event‐related features. Besides, since actual events not only develop during a period of time but also exist and advect over a range of spatial extents, further research should consider both the temporal and spatial event features, probably using a quasi‐Lagrangian framework to more accurately represent the meteorological events (Esmaili et al., 2016; Lochbihler et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, given the limitations of the study period, some results are calculated by gathering all the events from all the valid gridboxes across China, while a future study with a sufficient number of samples should further investigate the region‐specific event‐related features. Besides, since actual events not only develop during a period of time but also exist and advect over a range of spatial extents, further research should consider both the temporal and spatial event features, probably using a quasi‐Lagrangian framework to more accurately represent the meteorological events (Esmaili et al., 2016; Lochbihler et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This has, for example, been discussed in Esmaili et al. (2016), who presented a global cloud cluster tracking with unrealistically high amounts of convective cloud clusters over the TP during winter when only brightness temperatures are used. The atmospheric transmittance at wavelengths corresponding to the IR channels used for tracking (∼10.8 μm) is relatively high, while surface emissivity at these wavelengths is generally low for dry regions (Schädlich et al., 2001).…”
Section: Methodsmentioning
confidence: 98%
“…However, using universal thresholds can be problematic in a mountain environment like the TP, where low surface temperatures from high mountain tops can be confused with high cloud tops from deep convective clusters, particularly at night and during winter. This has, for example, been discussed in Esmaili et al (2016), who presented a global cloud cluster tracking with unrealistically high amounts of convective cloud clusters over the TP during winter when only brightness temperatures are used. The atmospheric transmittance at wavelengths corresponding to the IR channels used for tracking (∼10.8 μm) is relatively high, while surface emissivity at these wavelengths is generally low for dry regions (Schädlich et al, 2001).…”
Section: Tablementioning
confidence: 99%
“…Moreover, as shown in Table 2, the rate of incorrect filling decreases as the size of convective system grows. The likely reason for greater regime persistence from Terra to Aqua as the system grows in size is the longer lifetime of bigger systems (e.g., Chen & Houze, 1997; Esmaili et al, 2016). We also examined the geographical distribution of transition consistency of TCR1, TCR2, and TCR3 as a group from Terra to Aqua and found that the consistent transitions occurred more frequently in the warm pool oceans (not shown).…”
Section: Methodsmentioning
confidence: 99%